Frequency upconversion in a Pr(3+) doped chalcogenide glass containing silver nanoparticles - Rai, Vineet Kumar; de Araujo, Cid B.; Ledemi, Y.; Bureau, B.; Poulain, M.; Zhang, X. H.; Messaddeq, Younes [UNESP] (American Institute of Physics (AIP), 2008)
We report on orange-to-blue frequency upconversion (UC) in Pr(3+) doped chalcogenide glass (Ga(10)Ge(25)S(65)) doped with Ag(2)S and heat treated under different conditions to nucleate silver nanoparticles (NPs). The experiments were performed using 7 ns pulses from a dye laser that operates at similar to 590 nm, in resonance with the (3)H(4)->(1)D(2) transition of Pr(3+) ions. The enhancement observed in the UC emission at similar to 494 nm, ascribed as (3)P(0)->(3)H(4) transition of the Pr(3+) ion, is attributed to the large local field acting on the emitting ions due to the presence of the metallic NPs. (C) 2008 American Institute of Physics.